STUDY OF SOCIETY BEHAVIOR TO EARLY WARNING IN THE RAILWAY LEVEL CROSSING WITHOUT BARRIER IN GAYUNG KEBONSARI, SURABAYA - Adita Utami; Hera Widyastuti (BRIN, 2020)
Railway level crossing safety is one of the most critical issues for railways. Collisions between trains and motorized vehicles contribute most to LX accidents. Population growth and the development of economic in Indonesia affect the increase in vehicle volume, especially in the city of Surabaya. Furthermore, the increasing of vehicles volume, causing congestion at some points in Surabaya including Gayung Kebonsari railway level crossing. One of the congestion factors at the railway level crossings is the duration of closing time as the train passes through the crossing. The uncertain duration of gate closing time cause road users to be undisciplined by break through the crossing gates while the train pass through the crossings. Considering of those problems, respondentsâ€™ opinion is being evaluated to see the society behavior to early warning on reducing the number of traffic violation. A comprehensive discussion of the existing problems, lessons learned and the possible future implications that can be applied in Indonesia are presented.Â Key Words: Railway Level Crossing, Accident, Society Behavior, Regression, Binary logit